2002
DOI: 10.1677/joe.0.1730465
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 (GLP-1) and glucose metabolism in human myocytes

Abstract: Glucagon-like peptide-1 (GLP-1) has been shown to have insulin-like effects upon the metabolism of glucose in rat liver, muscle and fat, and on that of lipids in rat and human adipocytes. These actions seem to be exerted through specific receptors which, unlike that of the pancreas, are not -at least in liver and muscle -cAMP-associated. Here we have investigated the effect, its characteristics, and possible second messengers of GLP-1 on the glucose metabolism of human skeletal muscle, in tissue strips and pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(80 citation statements)
references
References 47 publications
3
76
1
Order By: Relevance
“…The present study demonstrated that the beneficial effects of exendin-4 were also found in CaMTg diabetic mice, and that its major effect was to maintain the b-cell mass, because 1) the exendin-4 treatment increased the insulin contents of the pancreas and islets and 2) it also expanded the insulin-positive area in both nTg and CaMTg mice. Although the extrapancreatic effects of GLP-1 have been reported to participate in the hypoglycemic effects of exendin-4 (Egan et al 1994, Luque et al 2002, Dardevet et al 2004), we could not find any effect of the treatment on plasma glucose levels in the insulin tolerance test.…”
Section: Discussioncontrasting
confidence: 75%
“…The present study demonstrated that the beneficial effects of exendin-4 were also found in CaMTg diabetic mice, and that its major effect was to maintain the b-cell mass, because 1) the exendin-4 treatment increased the insulin contents of the pancreas and islets and 2) it also expanded the insulin-positive area in both nTg and CaMTg mice. Although the extrapancreatic effects of GLP-1 have been reported to participate in the hypoglycemic effects of exendin-4 (Egan et al 1994, Luque et al 2002, Dardevet et al 2004), we could not find any effect of the treatment on plasma glucose levels in the insulin tolerance test.…”
Section: Discussioncontrasting
confidence: 75%
“…Nevertheless, in studies involving direct determination of lipolysis rates in human subcutaneous tissue, Bertin et al (16) were unable to find any effects of GLP-1. GLP-1 receptors have also been claimed to be present in rat skeletal muscle (49), and GLP-1 was reported to stimulate glucose metabolism in human myocytes (173). Similar observations were made in studies of L6 myotubes, and there was evidence that the effects were transmitted via receptors distinct from the classical GLP-1 receptor (336).…”
Section: Whole Body Effects Peripheral Effects and Effects On Inmentioning
confidence: 59%
“…On this basis, Ex9-39 is considered to be an inverse agonist of the GLP-1 receptor (26). In contrast, in some studies Ex9-39 does not antagonize GLP-1 action or may even behave as an agonist (27)(28)(29)(30). These observations raise the possibility that although Ex9-39 effectively antagonized the incretin effect of endogenous GLP-1, the growth-promoting effect was not antagonized.…”
Section: Glp-1 In Pancreatic Regenerationmentioning
confidence: 99%